Plasmon-induced trap filling at grain boundaries in perovskite solar cells - Yao, Kai; Li, Siqi; Liu, Zhiliang; Ying, Yiran; Dvořák, Petr; Fei, Linfeng; Šikola, Tomáš; Huang, Haitao; Nordlander, Peter; Jen, Alex K-Y; Lei, Dangyuan (Light, science & applications, 2021)
The deep-level traps induced by charged defects at the grain boundaries (GBs) of polycrystalline organic-inorganic halide perovskite (OIHP) films serve as major recombination centres, which limit the device performance. Herein, we incorporate specially designed poly(3-aminothiophenol)-coated gold (Au@PAT) nanoparticles into the perovskite absorber, in order to examine the influence of plasmonic resonance on carrier dynamics in perovskite solar cells. Local changes in the photophysical properties of the OIHP films reveal that plasmon excitation could fill trap sites at the GB region through photo-brightening, whereas transient absorption spectroscopy and density functional theory calculations correlate this photo-brightening of trap states with plasmon-induced interfacial processes. As a result, the device achieved the best efficiency of 22.0% with robust operational stability. Our work provides unambiguous evidence for plasmon-induced trap occupation in OIHP and reveals that plasmonic nanostructures may be one type of efficient additives to overcome the recombination losses in perovskite solar cells and thin-film solar cells in general.